Gambaran Implementasi Penggunaan Artificial Intelligence (AI) Pada Mahasiswa Jurusan Akuntansi Politeknik Negeri Bali - Ni Made Dian Kemala Ratih Palgunadi; Ni Made Dwita Ratnaningsih (Journal of Innovation Research and Knowledge, 2026)
This study aims to describe the implementation of Artificial Intelligence (AI) among students of the Accounting Department at Politeknik Negeri Bali by analyzing their awareness, readiness, and perceptions of AI use in academic activities. A descriptive research design with quantitative and qualitative approaches was employed. Data were collected through a questionnaire administered to 95 respondents selected using the Yamane formula and analyzed using descriptive statistics and content analysis. The findings reveal that most students are familiar with and actively use AI to support their academic activities, perceiving it as a tool that enhances learning effectiveness and efficiency. Students are also aware of the potential risks of AI, including overdependence, inaccurate information, and academic integrity issues. Although students demonstrate a good level of readiness to adopt AI, improvements in facilities, training, and institutional regulations are needed to ensure its optimal, ethical, and responsible use in higher education